Transforming Lives: The Power of Community Art in Bendungan Hilir's Dense Slum Housing - Muharrami, Aprilia; Dharmaraty, Ashri Prawesthi (Institut Seni Indonesia Bali, 2024)
The purpose of this study is to explore the impact of community art initiatives on improving living conditions and social cohesion in the dense slum housing of Bendungan Hilir. The research employs a qualitative approach, involving in-depth interviews with community members, local artists, and NGO representatives, as well as participatory observation. These methods allowed for a comprehensive understanding of how community art influences the environment and social dynamics in the area. The results demonstrate significant aesthetic improvements, enhanced social cohesion, reduced crime rates, and improved mental well-being among residents. Specifically, murals and art installations have made the area more vibrant and welcoming, fostering a sense of community and shared purpose. The beautification efforts are linked to a decrease in petty crimes, as the improved environment discourages vandalism and other criminal activities.